Effect of omega−3 fatty acdid supplementation on reduce body weight and body fat mass in obesity: A case study with an evidence-based approach - Anissa, Lidya; Lestari, Wiji (Indonesian Nutrition Association, 2025)
Background: Obesity is a public health problem, especially in developing countries. Providing Omega−3 supplementation has benefits to reduce body weight and body fat mass. Objective: This study aims to determine the effect of omega−3 supplementation on weight loss and body fat mass in obesity. Methods: This study used a literature search using advanced queries in the databases PubMed, Scopus, ProQuest, Cochrane Library, and combined MeSH terms with Title/Abstract. The collected literature is discarded if there are duplicates, then literature that meets the eligibility criteria is filtered. We used the Oxford Center for Evidence-Based Medicine as a means of critical appraisal and determining the level of evidence of the selected literature. Results: Four chosen study were selected. The first study involved 39 adults with obesity, there was a weight loss of 6.04 kg in the group given omega−3 supplementation of 6 g/day for 8 weeks compared to the placebo group 5.4 kg and there was a decreased in body fat mass in the intervention group. The second study did not show a significant result. The third study on 65 women showed a weight loss of 3.07 kg in the group given omega−3 consisting of 1.08 g EPA and 0.72 g DHA compared to 1.16 kg in the placebo group for 12 weeks. In the fourth study, a systematic review study, there was no conclusive result. Conclusion: Omega−3 fatty acid supplementation could be beneficial in reducing weight in obese patients with dietary modification.